The Effects of Resveratrol Supplementation on the Quality of Life of Diabetic Patients with Neuropathy: Small Randomized Clinical Trial - M. Amin, Gulabakh; Marouf, Bushra Hassan; Namiq, Hiwa (Iraqi Journal of Pharmaceutical Sciences, 2023)
The diabetic neuropathy complication exerts a considerable decline in the level of patient’s well-being. The main approaches to hamper the progression of diabetic complications and improve patient’s life quality are controlling the glycemic levels and amelioration of the hyperglycemia-induced neuroinflammation, oxidative stress and pain. Supplementation of appropriate anti-inflammatory and anti-oxidants such as resveratrol may therefore be effective in the management of diabetic complications. The aim of this trial was to assess resveratrol’s impact on improving life quality of patients with the neuropathic complication of diabetes. Sixty-one patients with diabetic neuropathy were recruited in this double-blinded placebo-controlled trial. Patients were randomized into the resveratrol (n=31) group; who received a 500mg resveratrol capsule once daily concomitantly with the conventional hypoglycemic agents for three months, and the placebo (n=30) group. From each group 25 patients completed the study. The quality of life (QoL) of the patients was estimated utilizing RAND 36-item survey questionnaire. Fasting blood glucose levels were analyzed at the baseline and on the last day of the 3rd month. There was a significant decrement (p< 0.001) in the fasting serum glucose level of the patients supplemented with resveratrol at the end of the 3rd month, in comparison with the patient using the placebo. There was also a significant improvement in patient’s severity of pain (p<0.001) as shown in the bodily pain score of the RAND 36 scale and a remarkable (p < 0.05) improvement in physical functioning, physical health, social functioning, emotional well-being, energy/fatigue, and health change subscales of the questionnaire. The study concluded that resveratrol is the polyphenol that has a positive effect on reducing pain associated with diabetic neuropathy and improving the overall QoL of the patient.